2018
DOI: 10.5696/2156-9614-8.19.180904
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Use on Concentrations of Potentially Toxic Elements in Urban Soils of Lagos, Nigeria

Abstract: Background.Among soil contaminants, potentially toxic elements (PTE) are of major significance because they are ubiquitous, toxic and persistent. Chronic exposure of humans to these elements has been linked with developmental delay, cancer, atherosclerosis and kidney damage, stomach ailments, respiratory problems, heart disease and cancer.Objectives.The present study aims to investigate current PTE concentrations in urban soils of Lagos, an example of a rapidly urbanizing megacity in a developing country. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Higher levels of heavy metal concentrations in soils from dumpsites and their ecological effects has been reported by several researchers (Akintola and Bodede, 2019b;Famuyiwa et al, 2018, Hu et al, 2018Akintola et al, 2020). Ajakanga dumpsite and its environ has been reported to have elevated concentrations of heavy metals due to anthropogenic influence of the wastes (Oguiseju et al, 2015;Ganiyu et al, 2016, Ewemoje et al, 2017Akintola and Bodede 2019a).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Higher levels of heavy metal concentrations in soils from dumpsites and their ecological effects has been reported by several researchers (Akintola and Bodede, 2019b;Famuyiwa et al, 2018, Hu et al, 2018Akintola et al, 2020). Ajakanga dumpsite and its environ has been reported to have elevated concentrations of heavy metals due to anthropogenic influence of the wastes (Oguiseju et al, 2015;Ganiyu et al, 2016, Ewemoje et al, 2017Akintola and Bodede 2019a).…”
mentioning
confidence: 63%
“…Solid wastes can decompose wide varieties of contaminants which can extensively affect the environment and human health (Sing et al, 2011). The improper management of waste dumpsites in many countries of the world has led to heavy metals contamination due to leachates that emanate from the decomposition of the deposited wastes (Akintola, 2014;Bartkowiak et al, 2016, Famuyiwa et al, 2018.…”
mentioning
confidence: 99%
“…In heavily commuted cities such as in Southwest Nigeria, metals deposit such as Cd, Cu, Pb and Zn are good indicators of contaminations from automobiles as they appear in gasoline, oil lubricants, car component and industrial incinerator emissions [32]. Numerous studies conducted in recent years found high levels of heavy metals as street dust contaminants near traffic routes in Southwest Nigeria [24,35,36]. The re-suspension of metal-laden road dust may also be identified as the main source of road pollution, especially along roads with intense traffic and high vehicular emission.…”
Section: Heavy Metals Accumulation In Soilmentioning
confidence: 99%
“…Ninety (90) soil samples (30 from each area) were collected from Iwaya, Maroko, and Ilaje between January and June 2020. The samplings were done randomly at a depth of 0-10 cm [30] into clean and pre-sterilized polyethylene bags, labelled appropriately, and transported to the laboratory. The samples were air-dried at room temperature (29 °C) for 6 days, and later oven-dried until constant weights were attained [31].…”
Section: Soil Sample Collection and Preparationmentioning
confidence: 99%